Utilization of the WhatsApp-Based Internet for Elementary School Students during the Covid-19 Pandemic - Pertiwi, Novalda; Saud, Udin Saefuddin; Saffitri, Yoesrina Novia Vini (International Conference on Elementary Education, 2021)
At this time internet has become one of a necessity for every human being, even up to elementary school student. Internet is used as a place to share information and communication, one of the applications that can be used is WhatsApp. WhatsApp is a long-distance massager application that is almost used by people around the world, especially during the Covid-19 pandemic which requires all activities to be carried out at home, including school activities. Therefore, this article aims to discuss the use of the WhatsApp application in learning for elementary school students during the Covid-19 pandemic. Through this study, during the Covid-19 pandemic, the use of the WhatsApp-based internet was useful as a means of communication between teacher-students, teacher-teachers, and teacher-parents. Besides, the WhatsApp application is also useful as a medium for sharing information about materials and tasks that must be completed at home. Thus, WhatsApp has become an important part of the learning process during the Covid- 19 pandemic. This research was conducted using the literature study method, which is to collect journals related to the use of WhatsApp in learning during the Covid-19 pandemic.